2022
DOI: 10.1111/jace.18354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thermodynamic stability of sapphire in eutectic molten chloride environment

Abstract: The continued development of molten salt reactors and concentrated solar power plants requires highly efficient and stable instruments that can efficiently monitor the chemical conditions of the molten salt during long‐term operation in both the fuel and coolant/heat transfer fluid loops. Sapphire (Al2O3) fibers have shown tremendous potential due to inherent radiation resistance and a broader operational range of temperature. In this work, computational thermodynamic modeling (CALPHAD) using the ThermoCalc so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…21 Recently it was also shown that sapphire (Al 2 O 3 ) fibers with Mo and Ni can provide a protective coating in chloride-based salts. 22 For the construction of reference electrodes to be used in the DOR process, compatibility with CaCl 2 , CaO, and Ca is needed. Given the high thermodynamic stability of CaO, we sought to find ceramics with comparable stability that could be obtained in commercially available ceramic tubes.…”
Section: + = + [ ] Puomentioning
confidence: 99%
“…21 Recently it was also shown that sapphire (Al 2 O 3 ) fibers with Mo and Ni can provide a protective coating in chloride-based salts. 22 For the construction of reference electrodes to be used in the DOR process, compatibility with CaCl 2 , CaO, and Ca is needed. Given the high thermodynamic stability of CaO, we sought to find ceramics with comparable stability that could be obtained in commercially available ceramic tubes.…”
Section: + = + [ ] Puomentioning
confidence: 99%